2020
DOI: 10.3389/fneur.2020.604445
|View full text |Cite
|
Sign up to set email alerts
|

Different Targets of Monoclonal Antibodies in Neuromyelitis Optica Spectrum Disorders: A Meta-Analysis Evidenced From Randomized Controlled Trials

Abstract: Background: Neuromyelitis optica spectrum disorder (NMOSD), an autoimmune inflammatory disorder of the central nervous system, often leads to vision loss or paralysis. This meta-analysis focused on the assessment of the monoclonal antibody therapy in NMOSD and compared different targets of monoclonal antibodies with each other in terms of efficacy and safety outcomes.Method: We searched through the databases of MEDLINE, EMBASE, Central Register of Controlled Trials (CENTRAL), and clinicaltrials.gov for randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
1
5
0
1
Order By: Relevance
“…Though there is difference in the frequency but, most of the common side effects are similar. The frequency of most common adverse events like Upper respiratory tract infections, Urinary Tract Infections, hypercholesterolemia, and serious adverse events are similar to studies by Xie et al and Xue et al [ 28 , 29 ] Though, cardiovascular disease is the main safety of concern in Anti-Interleukin-6 receptor inhibitors like Satralizumab and Tocilizumab as a result of an increase in cholesterol levels; recent trials [ 20 ] have shown no increase in the risk of cardiovascular disease [ 30 ]. No mortality was observed in two trials of Satralizumab in comparison to two treatment related deaths in Tocilizumab used studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Though there is difference in the frequency but, most of the common side effects are similar. The frequency of most common adverse events like Upper respiratory tract infections, Urinary Tract Infections, hypercholesterolemia, and serious adverse events are similar to studies by Xie et al and Xue et al [ 28 , 29 ] Though, cardiovascular disease is the main safety of concern in Anti-Interleukin-6 receptor inhibitors like Satralizumab and Tocilizumab as a result of an increase in cholesterol levels; recent trials [ 20 ] have shown no increase in the risk of cardiovascular disease [ 30 ]. No mortality was observed in two trials of Satralizumab in comparison to two treatment related deaths in Tocilizumab used studies.…”
Section: Discussionsupporting
confidence: 84%
“…Sub-group analysis of this study found a significant decrease in on-trail relapse risk and EDSS at follow-up (analysis of two trials of Satralizumab) but non-significant difference in mean ARR among the treatment groups and placebo group. IL-6 inhibitors were also found to be superior to other monoclonal antibodies in reducing EDSS [ 28 ]. A meta-analysis describing the safety and efficacy of Tocilizumab has similar therapeutic outcomes as compared to our analysis considering results in a change in mean ARR and EDSS score following treatment as only more studies of Tocilizumab treatment were added in our analysis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aligned with RTX, these medications were developed based on the pathophysiology of NMOSD, three of which (eculizumab, inebilizumab, and satralizumab) have been approved by the FDA to treat NMOSD. The pooled studies 4749 found that there were no significant AE or SAE differences among these monoclonal antibodies (including RTX), no AE increased when comparing with placebo or AZA, and few deaths occurred. In other major immune-related diseases, most AEs of RTX were mild or moderate, 5052 so that they could be solved by symptomatic treatments such as reducing the drug infusion rates, providing minor supportive treatments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant correlation was found between the proportion of relapse-free patients and tocilizumab treatment ( 51 ). Another meta-analysis involving 775 patients from seven randomized controlled trials found that patients treated with tocilizumab or satralizumab exhibited significantly lower EDSS scores compared with patients treated with other monoclonal antibodies ( 52 ). Meanwhile, in a meta-analysis comprising a total of 202 patients with NMOSD from nine studies, Kharel et al.…”
Section: Tocilizumabmentioning
confidence: 99%